The Development and Validation of the Client Expectations of Massage Scale - Boulanger, CMT, PhD, Karen T.; Campo, PhD, Shelly; Glanville, PhD, Jennifer L.; Lowe, DrPH, John B.; Yang, PhD, Jingzhen (International Journal of Therapeutic Massage & Bodywork, 2012)
Background: Although there is evidence that client expectations influence client outcomes, a valid and reliable scale for measuring the range of client expectations for both massage therapy and the behaviors of their massage therapists does not exist. Understanding how client expectations influence client outcomes would provide insight into how massage achieves its reported effects.Purpose: To develop and validate the Client Expectations of Massage Scale (CEMS), a measure of clients’ clinical, educational, interpersonal, and outcome expectations.Setting: Offices of licensed massage therapists in Iowa.Research Design: A practice-based research methodology was used to collect data from two samples of massage therapy clients. For Sample1, 21 volunteer massage therapists collected data from their clients before the massage. Factor analysis was conducted to test construct validityand coefficient alpha was used to assess reliability. Correlational analyses with the CEMS, previous measures of client expectations, and theLife Orientation Test–Revised were examined to test the convergent and discriminant validity of the CEMS. For Sample 2, 24 massage therapistsdistributed study materials for clients to complete before and after a massage therapy session. Structural equation modeling was used to assess the construct, discriminant, and predictive validity of the CEMS.Participants: Sample 1 involved 320 and Sample 2 involved 321 adult massage clients. Intervention: Standard care provided by licensed massage therapists.Main Outcomes: Numeric Rating Scale for pain and Positive and Negative Affect Schedule– Revised (including the Serenity subscale).Results: The CEMS demonstrated good construct, convergent, discriminant and predictive validity, and adequate reliability. Client expectations were generally positive toward massage and their massage therapists. Positive outcome expectations had a positive effect on clients’ changes in pain and serenity. High interpersonal expectations had a negative effect on clients’ changes in serenity.Conclusions: Client expectations contribute to the nonspecific effects of massage therapy.